PENINGKATAN KADAR KOLESTEROL PADA LANSIA DI PEDESAAN MENGWI: STUDI DESKRIPTIF CROSS-SECTIONAL - Bekti, Heri Setiyo; Suwarriana, I Nyoman Astra; Arjani, Ida Ayu Made Sri (Poltekkes Kemenkes Malang, 2022)
Increased cholesterol levels are one of the causes of coronary heart disease in most of the elderly. The purpose of this study was to describe total cholesterol levels in the elderly in mengwi village. The research method used is descriptive, the research was carried out from January to April 2021 with a total of 27 respondents obtained by purposive sampling technique. total cholesterol levels were measured by the point of care testing poct method. The results showed that of 27 respondents 59.3Percent had normal total cholesterol levels, 37 Percent threshold total cholesterol levels, and 3.7Percent high total cholesterol levels. abnormal total cholesterol is more commonly found in the age range of 71 until 75 years and is more experienced by elderly women 22.2 Percent. Based on the consumption of fatty foods, 51.9 Percent of the elderly rarely consume fatty foods and 37Percent of the elderly who have abnormal total cholesterol levels and are included in the category of frequently consuming fatty foods. Based on the results, it can be concluded that most of the elderly have normal total cholesterol levels. Abnormal total cholesterol levels are more common in the age range of 71 until 74 years and are more experienced by elderly women and 37 Percent of the elderly, including frequent consumption of fatty foods